An estimation of the coupling coefficient of the series inductive resonant wireless power transfer coils - Adam, Ismail; Khan, Sheroz; Zaharudin, Zarimin; Abdul Kader, Kushsairy; Nordin, Anis Nurashikin; Yaacob, Mashkuri (Universiti Teknikal Malaysia Melaka, 2020)
Though the power transfer efficiency of the inductive resonant wireless power transfer is relatively high, the power transfer efficiency of the inductive resonant wireless power transfer is undoubtedly depending on the coupling coefficient. Coupled with the coupling coefficient, the highest possible power transfer efficiency can be achieved by controlling the operating frequency with impedance matching. Therefore, the relationship of the input impedance to the variation of the coupling coefficient is of paramount importance in maintaining the highest possible power transfer efficiency for a given coupling coefficient. This paper presents the relationship of the input impedance of the series-to-series inductive resonant wireless power transfer to the variations of the coupling coefficient. The analysis is carried out by using the T-equivalent circuit, producing analytical results for comparison and validation by equivalently obtained simulation results, guarantying the maximum power transfer efficiency for a typical series-to-series inductive resonant link. The modeling validity is shown by percentage error in between the analytical and simulation results. The novelty of this paper is in the simplicity of the coupling coefficient estimation by reference to the input impedance